(untitled) (Desenvolvimento em Questão, 2020)
Facing the socioeconomic and environmental crisis, community-based tourism (TBC) represents an alternative to development that aims to conserve natural resources, promoting the well being of communities through income generation and social inclusion. The objective of this study is to investigate the main challenges and possibilities for the development of community-based tourism in the São Gonçalo Beira Rio riverside community, a landmark in the city of Cuiabá-MT. Methodologically, we opted for field research; as a situational analysis tool, the Swot matrix and Foucault’s discourse analysis. The preliminary results lead us to believe that the locality of São Gonçalo Beira Rio presents possibilities for the development of TBC, as opposed to the wealth of knowledge and ways of life of this community. However, due to the complexity and the many variables identified, collective planning will be necessary, starting with the sensitization, mobilization and qualification of the actors involved, as well as adoption of strategies community involvement in order to obtain better results.